Kingdom of Lesotho : Request for a Three-Year Arrangement Extended Fund Facility Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; Statement by the Executive Director for the Kingdom of Lesotho. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Lesotho's fiscal and external balances have deteriorated as a result of the global economic downturn and a surge in spending. Undertaking key fiscal adjustments to restore macroeconomic stability is necessary for raising Lesotho's growth potential. Executive Directors commend the measures taken in the budget to reduce expenditure. Further strengthening of debt management and accelerating structural reforms is crucial for raising Lesotho's growth potential. Strengthening the institutional and regulatory framework for banks and non-bank financial institutions (NBFIs) will help to support financial sector health and stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet